Kontribusi Guru Pendidikan Agama Islam (PAI) dalam Kegiatan Belajar Al-Qur’an pada Siswa MTs Darul Fatihin NW Gerintuk Desa Boyemare Kecamatan Sakra Barat - Abd Quddus Al Badani (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2024)
This study aims to determine the role of Islamic Religious Education teachers in Al-Quran learning activities and to determine the obstacles and solutions faced by Islamic Religious Education teachers in helping students learn the Al-Quran. The method used is a qualitative approach. Data collection techniques use interview techniques, documentation and observation. Data analysis in this study uses data reduction, data presentation, verification and drawing conclusions. From the results of the study it was found that teachers act as teachers, educators, and leaders. Teachers use the iqro' method, listening and repeating with a learning strategy using peer tutors, as educators teachers are able to foster discipline and good morals in students, and as leaders teachers are able to create a comfortable learning atmosphere. The obstacles and solutions faced by Islamic Religious Education are the obstacles of limited learning time in class, the level of student ability is lacking, the lack of assistant teachers and adequate facilities. The solutions made by Islamic Religious Education teachers include the formation of an Al-Quran learning program outside of regular class hours, scheduling special time for additional study in the hall, utilizing smarter students as assistant teachers, using additional spaces such as gazebos and school corridors, and efforts to get assistance from the government to improve the infrastructure for learning the Al-Quran.